ANALISIS DAMPAK PENYALURAN DANA ZISWAF MELALUI LEMBAGA KEUANGAN SYARIAH TERHADAP STABILITAS DAN KINERJA KEUANGAN - Adis Natasya Faradila; Zahra Alfiana; Bella Rahma Dewi; Mohammad Soleh (LPPM IAI Nazhatut Thullab, 2025)
This study analyzes the impact of ZISWAF (Zakat, Infaq, Sedekah, and Waqf) fund distribution through Islamic financial institutions on financial stability and performance in Indonesia, amidst potential funds reaching IDR 233 trillion, but realization of only tens of trillions due to the dominance of consumer funds and weak governance. The study aimed to identify the integration mechanism of ZISWAF with Islamic finance and its implications for NPF, ROA, and Third Party Funds (DPK) indicators based on a content analysis of OJK documents for the 2020-2024 period. The method used was descriptive qualitative research using content analysis techniques on official financial reports, OJK publications, and Islamic institutional documents. The results showed a positive correlation between productive ZISWAF distribution and a decrease in NPF below 3%, an average increase in ROA of 1.8%, and 15% year-on-year growth in DPK through portfolio diversification and blended waqf finance. Although challenges of dependency on beneficiaries and fragmentation between institutions still hamper optimization. These findings recommend OJK regulations for integrated reporting standards and a minimum allocation of 60% of funds to productive schemes to strengthen the resilience of the national Islamic financial sector.